PENGARUH TOTAL ASSET TURN OVER, CURRENT RATIO, PRICE EARNING RATIO DAN DEBT TO ASSETS RATIO TERHADAP HARGA SAHAM SEBELUM DAN SESUDAH COVID-19 - Hidayat Hidayat; Samryn Samryn (CV. Denasya Smart Publisher, 2024)
The COVID-19 pandemic has caused company share prices to experience significant fluctuations in a relatively short time span. Unstable economic conditions, changes in market demand, and changing government policies have all contributed to stock price volatility. Apart from that, global economic uncertainty, including in Indonesia. The cement industry is one of the sectors that has been impacted by COVID 19. Therefore, analysis of financial performance before and after COVID 19 on share prices in cement companies listed on the Indonesia Stock Exchange is important to study. This research found that financial performance had a significant effect on share prices in cement companies listed on the Indonesia Stock Exchange before and after the COVID-19 pandemic.